Paying for Our Periods: The Campaign to Tackle Period Poverty and End the Tampon Tax in the UK - Coryton, Laura Agyropulo; Russell, Lucy Marie (Columbia Journal of Gender and Law, 2021)
Tampon tax and period poverty activist movements are growing in tandem worldwide. These movements are reshaping the way we think about menstruation and what governments can do to tackle period-based injustices. Through this Essay, two United Kingdom (UK) period activists will explore how these UK movements were erected, how they interact with the global movements, and how Brexit has impacted UK menstruation activism and law-making. Finally, they will look ahead to discuss what they believe the future of period activism might look like.